Antibacterial Activity of Aqueous and Alcohol Extracts, of Selected Medicinal Plants and Vitamin Profiling Identification by HPLC - M. H. Shoker, Roaa; Jabbar Shamkhi, Israa; Hussein Raheema, Rana (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: Urinary tract infections (UTIs) represent a significant global health concern, often complicated by the increasing resistance of uropathogens to conventional antibiotics. Objective: This study investigates the antibacterial efficacy and vitamin content of different extracts of Sesamum indicum (sesame) and Pimpinella anisum (anise) against common UTI-causing bacteria, including Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Acinetobacter baumannii. Material and Methods: Plant seeds (P. anisum L. and S. indicum L.) were sourced locally, cleaned, ground, and used for aqueous, and alcoholic using standard maceration, distillation, and concentration methods. Bacterial isolates from UTI patients were identified and tested for antibiotic sensitivity. Antibacterial activity was assessed via agar well diffusion, and vitamin content in extracts was analyzed by HPLC. Results: Indicated that alcoholic extracts, particularly from P. anisum, exhibited the highest antibacterial activity, with inhibition zones reaching up to 19.20 ± 1.095 mm against E. coli. K. pneumoniae was the most susceptible pathogen, while A. baumannii showed the greatest resistance. High-Performance Liquid Chromatography (HPLC) analysis revealed that both plants contained essential water-soluble (vitamins B1, B2, and C) and fat-soluble (vitamins A, D3, E, and K) vitamins. P. anisum demonstrated a higher total concentration of both vitamin groups compared to S. indicum. Conclusion: These findings support the potential of S. indicum and P. anisum as natural sources of bioactive compounds with antibacterial properties and nutritional value, suggesting their use as complementary therapies in the management of UTIs.